Actinic keratosis: a clinical and epidemiological revision Queratoses actínicas: revisão clínica e epidemiológica - Juliano Vilaverde Schmitt; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2012)
Actinic keratoses are benign intraepithelial skin neoplasms constituted by atypical proliferation of keratinocytes that may evolve to squamous cell carcinoma. They develop in photoexposed skin areas; they are induced mainly by ultraviolet radiation and are considered cutaneous markers of chronic exposure to sunlight. They develop mainly in adults and older, fair skinned individuals, and are the fourth most common cause of dermatologic consultation in Brazil. Damage to the apoptosis pathway in photoexposed epithelium favors cellular proliferation and the permanence of the lesions. In this revision, the authors assemble the main epidemiological data regarding this disease and suggest that strategies to identify risky phenotypes, early diagnosis, adequate treatment, clinical follow-up, stimulus to skin self examination, photoeducation and photoprotection should be promoted with the aim of avoiding the progression to malignancy and also the prevention and the diagnose of concomitant neoplasms also induced by ultraviolet radiation. Queratoses actínicas são neoplasias benignas intraepiteliais formadas por proliferações atípicas de queratinócitos com potencial de transformação em carcinoma espinocelular. Desenvolvem-se em áreas fotoexpostas da pele, são induzidas principalmente pela radiação ultravioleta e constituem marcadores de exposição solar crônica. Acometem indivíduos adultos e idosos, de fototipos claros, representando o quarto diagnóstico dermatológico mais comum no Brasil. Danos nas vias de apoptose do epitélio fotoexposto favorecem a proliferação celular e manutenção das lesões. Nesta revisão os autores reúnem os principais dados epidemiológicos sobre a doença e defendem que estratégias de identificação de fenótipos de risco, diagnóstico precoce, tratamento adequado, seguimento clínico, incentivo ao autoexame da pele, fotoeducação e fotoproteção devem ser promovidas, a fim de evitar a evolução das lesões, e também prevenir e diagnosticar neoplasias concomitantes também induzidas pela radiação solar.